Factors influencing menstrual problems and its effect on school attendances among adolescent girls in Myagdi, Nepal. - Rana, Sarita (2020)
EXECUTIVE SUMMARY: Introduction: Menstruation is a natural and biological process experienced by all adolescent girls and women in reproductive age. Adolescent girls throughout Nepal and the world face the many menstrual-related problems that harm their academic performance including school attendance and learning opportunities. The higher prevalence of menstrual problems can be attributed to inadequate dietary habits and lack of physical exercise, as most frequently affecting factors among adolescent girls. The objectives of this study were to determine the factors influencing menstrual problems and the effect of such problems on school attendance among adolescent girls. Methods: A cross-sectional study was conducted in secondary level schools of Myagdi, Nepal, adopting mixed methods of data collections among adolescent girls. Three schools were purposively selected, and a self- administered anonymous structured close-ended questionnaire was used to collect the quantitative data from 216 schoolgirls. Similarly, Focus Group Discussion (FGD) guideline was used to collect the qualitative data via three FGD from 27 girls who had their menarche took part. Qualitative data were analyzed thematically while quantitative data were analyzed using Statistical Package for Social Science version 23.1. Frequency, proportion, mean, standard deviation, and Pearson's Chi-square (x2) test were among the major statistical computation Results: The mean age of participant's was 13.81±1.387 years (range from 10-19 years). The study found that 41.2% of the girls used to remain absent at school during their menstruation while dysmenorrhea was reported by 84.2%. Inadequate dietary habits (71.0%) and lack of exercise (55.9%) were the major factors associated with different menstrual problems. Similarly, a significant association was found between various menstrual problems with school absenteeism Conclusion: The study indicated a positive relationship between various factors with menstrual problems and school absenteeism. Therefore, the study recommended that there should be a modification of lifestyle like adequate dietary habits, regular physical exercise by emphasizing the school health programs including reproductive health education to improve menstrual health. Keywords: Adolescent girls; Menstruation problems; Effects; School attendance